Community Empowerment Concept Based on Community Needs and Local Resources - Malta (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The community empowerment approach in development positions people centrally as both actors and beneficiaries, requiring active involvement in identifying needs, formulating strategies, and implementing solutions tailored to local conditions. By placing the community as the main actor, this approach aims to create a sustainable development process where individuals gain not only the results but also an understanding of the process itself, fostering long-term capacity for addressing challenges. Efforts to empower communities also focus on enhancing human resource quality and promoting behavioral changes across various dimensions, such as economic, social, and environmental aspects. This study aims to analyze the effectiveness of community empowerment as a strategy to achieve a more independent and sustainable quality of life. This study employs a qualitative approach to deeply explore community empowerment strategies as a critical component of sustainable development. This research then found that community empowerment should focus on building an economic base rooted in reliable local needs and resources, not just on increasing income. Successful empowerment is evident through creating strategic organizations and networks that enhance access to market information and technology. Furthermore, strengthening technical and managerial skills within the community, as well as the competencies of facilitators is essential to achieving sustainable independence and prosperity.